Experimental paracoccidioidomycosis in the syrian hamster: Morphology, ultrastructure and correlation of lesions with presence of specific antigens and serum levels of antibodies - Iabuki, Kunie [UNESP]; Montenegro, Mario R. [UNESP] (Springer Nature, 1979)
Male hamsters (134) received intratesticular injection of a live cerebriform culture of Paracoccidioides brasiliensis and were sacrificed from 6 hours up to 123 days onwards. Tissues from testis, lymph nodes, lungs, liver, spleen, kidneys and intestines were examined microscopically; presence of specific antigens was saught in lesions of testis, regional lymph nodes and liver by indirect immunofluorescence (IF); inoculation site lesions were studied electron microscopically and circulating specific antibodies measured by complement fixation and IF tests. Up to 24 hours inoculation site lesions showed fungi surrounded by PMNs; 48 hours latter macrophages accumulated forming loose nodules; epithelioid granulomata appeared after 5 days. Fungi, scarce in early lesions, increased in numbers up to the time when epithelioid granulomata dominated the picture; in young granulomata fungi were abundant and small; older granulomata contained rare, vacuolated fungi. Ultrastructurally the space between fungi and host-cells was larger around reproducing forms decreasing in size as the parasites grew larger and being a virtual slit around old degenerated fungi. Immunofluorescence studies revealed that fungal walls were brightly fluoerescent; in early lesions macrophages surrounding fungi or free in the intersticium contained fluorescent antigenic material in the cytoplasm; similar macrophages were observed in draining lymph nodes as early as 18 hours after inoculation, and latter, in macrophage nodules and Kupffer cells in the liver; epithelioid and giant cells appear to block diffusion of antigens, since in epithelioid granulomata fluorescence was limited to fungal walls. Disseminated paracoccidioidomycosis occurred in 100% of animals after day 5 of infection. Besides specific lesions (containing fungi), antigens were identified by immunofluorescence in 'non specific' lesions in the liver (diffuse or nodular Kupffer cell hyperplasia) and in the lymph nodes (histiocytic hyperplasia). Serum antibodies appeared in low titers, up to day 20, increasing onwards. From day 70 on, titers decreased and lesions changed from confluent epithelioid to loose granulomata infiltrated by PMNs; fungi that before were large and quiescent now were small and in active reproduction. Secondary amyloidosis was present in 85% of the animals. In the hamster, Paracoccidioidomycosis develops as a chronic progressive disease and the lesions are related both to fungi and its antigens. © 1979 Kluwer Academic Publishers.